Идея всеславянского единства и Первый Славянский конгресс в Исповеди Михаила Бакунина - Łucewicz, Ludmiła (Acta Polono-Ruthenica, 2018)
In the spotlight of the author there is a Confession of Mikhail Bakunin that is the unique personal, historical and political document. The letter was created by the prisoner of the Petropavlovsk fortress, state prisoner, and in the past one of the most committed Russian philosophers-Hegelians on the demand of the emperor Nikolay I. In the article it is considered: 1) an idea of Slavic unity, as it was understood by the Russian radical thinker; it was aimed to complete the destruction of all existing empires where Slavs lived: Ottoman, Austrian, Russian; and create the Great free Slavic federation on their ruins, with the capital in Constantinople; 2) the problems, considered by Bakunin in connection with organization and realization of the First Slavic Congress in Prague in 1848 (prehistory, cultural constituent, structure, lay-out of political forces and interests, fight of parties, national opposition); 3) the negative attitude of Bakunin towards modern Russia and her claims on all-Slavic domination; as well as the general negative opinion about the Congress.